I sentieri dell'università I percorsi nell'istruzione terziaria in Sardegna - Porcu, Mariano (UNICApress, 2023)
The Report analyzes the university careers of Sardinian students matriculated between 2010 and 2020 in a three-year or single-cycle degree program. Using microdata from the National Student Registry integrated with other sources, two junctures of university life are considered: the school-university transition and career outcomes after four years from matriculation considering the events graduation, dropout, change of course/university, and continuation of studies in a master's degree program. Data on university careers were treated according to two perspectives of analysis. In the first, data on Sardinian students are used to compare the characteristics of those enrolled in a Sardinian university with those who decided to matriculate in another region. In the second, the characteristics of students enrolled in a Sardinian university are compared with those enrolled in other Italian universities. The comparisons are made considering different characteristics of the students such as gender, educational background with reference to the type of high school attended and graduation grade, family socioeconomic background, and characteristics of the areas of origin.